Development of Malaysian Ethnobotanical Online Database - Roshaizi, Nur Athirah; Omar, Mohd Shahir Shamsir; Mustapha, Aida (Journal of Sustainable Natural Resources, 2022)
The existing Malaysian ethnobotanical database is not sufficiently comprehensive and may hinder sharing of ethnobotanical knowledge. The lack of interest and documentation especially in digitalizing prior knowledge is a worrying trend since Malaysia possess high ethnicity and abundance of biodiversity. It is crucial to preserve and digitalize the comprehensive ethnobotanical database as it gives benefits worldwide. This study aimed to identify online database features and data type for an ethnobotanical database, to collect and populate existing database via secondary data and to test the acceptance of the database by users by testing whether the database fulfil the requirements of a good ethnobotanical database. Rapid Prototyping method has been used in this study involving User Requirement Analysis and data acceptance test to construct and create the best ethnobotanical database. MYETHBO is the database created by using the Omeka Classic management system with Darwin Core standard. There are 1,074 plants information are collected online and mostly referred GlobinMed and GBIF. In this study, 30 plant species has been setup as exemplar pages. This study successfully developed a comprehensive ethnobotanical database (MYETHBO) by being able to identify the database features and data type needed via the Rapid Prototyping method, collect and populate existing data via secondary data and test the acceptance of the database by distributing the questionnaire to lecturers. MYETHBO will be beneficial to researchers, students and public people to gain knowledge of ethnobotany. It is available at https://cercom.uthm.edu.my/myethbo/.